The Level of Superstitious Thinking among University Students - Hama, Ahmad A.; Fatah, Bakhtiar I. (Humanities Journal of University of Zakho, 2024)
Superstition as a culture has mythological and historical roots, and it is difficult to remove so easily among individuals in society. This study aims to measure the prevalence of superstitious thought among students and find the most important superstitious thought among university students. According to the variables (gender, place of residence, and specialty ) the descriptive method was used to describe superstitious thoughts among university students, the research community is the students of Sulaimani University and (378) students were taken as a sample. The researchers prepared a scale consisting of (27) items after obtaining the truth and stability of the scale and analyzing the data the results show that Superstitious thoughts dominate the thinking of university students. Superstitious thoughts are more among female students than male students and more among students who live in urban areas and It is lower among students in scientific colleges than in medical and humanities colleges.